Information Systems and Strategic Planning: Exploring the Influence of Strategic Information Systems Planning on Corporate Operations (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In many businesses, strategic information and system planning is a widely established method. Such businesses have in common discussions with business strategy managers, model architecture of the general information system and projects over several years specified in the document entitled “Strategic Information System Plan.” Who requires this document, understands it, and decides on the future development of information systems and how it fulfils existing business demands? Strategic information systems planning (IS) has recently been an important issue for the IS and IT deployment in business systems, both researchers and practitioners. Recent studies have indicated that IT has less influence than was predicted on the efficiency of corporate operations. The evolution of IT and IT systems may thus not only be the challenge for system analyzers and IT specialists but also one of the main issues for the top management. The effectiveness of IT delivery depends on the information system's strategic strategy.